2011
DOI: 10.1007/s10641-011-9869-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation between collections of hatchery and wild masu salmon (Oncorhynchus masou) inferred from mitochondrial and microsatellite DNA analyses

Abstract: There has been very little effort to understand genetic divergence between wild and hatchery populations of masu salmon (Oncorhynchus masou). In this study, we used mitochondrial (mt) NADH dehydrogenase subunit 5 gene (ND5) and six polymorphic nuclear microsatellite DNA loci to compare the genetic variability in three hatchery broodstocks of masu salmon with the variability in eight putative wild masu populations sampled in five rivers including one known source river for the hatchery broodstocks. Both ND5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…To determine genetic distances among farms, the data were examined using the chord distance ( D C ) method of Cavalli‐Sforza and Edwards (). This method has been widely used to calculate genetic distance in captive and wild populations of marine and freshwater species (Bai et al ; Iwamoto et al ; Yu et al ). The neighbor‐joining dendrogram resulting from this analysis was corroborated statistically by a bootstrap analysis of 1000 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…To determine genetic distances among farms, the data were examined using the chord distance ( D C ) method of Cavalli‐Sforza and Edwards (). This method has been widely used to calculate genetic distance in captive and wild populations of marine and freshwater species (Bai et al ; Iwamoto et al ; Yu et al ). The neighbor‐joining dendrogram resulting from this analysis was corroborated statistically by a bootstrap analysis of 1000 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial markers are currently one of the most popular molecular markers, particularly in studies of molecular evolution, species identification, and genetic diversity (Yu et al, 2012;Sahoo et al, 2015;Korkmaz et al, 2016). The mitochondrial genome is usually a closed circular molecule, and contains 13 protein-coding genes, 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and a control region.…”
Section: Introductionmentioning
confidence: 99%
“…Complete mitochondrial genome sequence information is useful in studying genome-level characteristics and phylogenetic relationships (Knudsen et al, 2006), because of its high mutation rate, simple structure, abundant distribution, and maternal inheritance (Yu et al, 2012;Ma et al, 2013;Baek et al, 2014). With the development of molecular techniques, it has become easier to obtain complete mitochondrial genome sequences (Wang et al, 2015), and they have been reported in many crustacean species (Shen et al, 2007;Liu and Cui, 2010;Jondeung et al, 2012;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%